Distributed robust beamforming algorithm for spectral coexistence in satellite and high altitude platform networks - Zining WANG; Min LIN; Fei LI; Lve HAN; Weiping ZHU (Tongxin xuebao)
A distributed robust beamforming (BF) algorithm was proposed to improve spectrum efficiency for an integrated satellite and high altitude platform (HAP) network.Specifically, for the scenario where satellite network and HAP network adopted multicast and NOMA to serve their respective multiple users, an optimization problem was formulated to maximize the sum rate, subject to the rate requirements of both satellite and aerial terminals, and the transmit power budget of satellite and aerial platforms.Then, by considering both the imperfect channel state information (CSI) and the imperfect successive interference cancellation (SIC), S-procedure and sequential convex approximation were adopted to transform the nonconvex problem, and then a distributed BF algorithm using Lagrange duality was proposed to enable the spectral coexistence.Finally, simulation results demonstrate that the proposed algorithm can achieve a similar performance yet at a lower signaling overhead compared with the other existing works.